RENT ACCOUNTING SYSTEM AS AN INTERNAL CONTROL EFFORTS: Study on the Public Housing Department of the Blitar City - Novia Ekasari Mukti; Endah Masrunik; Diana Elvianita Martanti (Universitas Islam Balitar, 2018)
This study aims to describe how the flow of the accounting system for leasing goods as an internal control effort used by UPT Rusunawa is in accordance with the accounting system theory and internal control. This research method uses descriptive qualitative method using observation, interview, documentation and literature study techniques. Data analysis techniques are used triangulation techniques. The sample in this study is UPT Rusunawa, Public Housing Office, Blitar city. The results of this study, namely the rental accounting system and internal control at the Flat Unit UPT in practice there are still less in accordance with the theory. This is because there are multiple tasks in the administration. The administration section here is also part of the payment. But in its implementation the system that has been implemented has been going well because every process carried out has been very detailed